2014
DOI: 10.1002/joc.4027
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of tropical storm and hurricane tracks in the North Atlantic basin using a sinuosity‐based approach

Abstract: Quantitative analysis is carried on the shape of over 420 tropical storm and hurricane tracks in the North Atlantic basin for the period 1965–2011. A sinuosity metric is used as the basis for track morphometry, applied to best‐track data accessed from the IBTrACs archive maintained by NOAA. GIS tools, track mapping according to sinuosity category, and various statistical analyses permit temporal and spatial patterns in track shape to be identified and investigated. Temporal analysis reveals no underlying long‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…This cluster is consistent with Ramsay et al (2012) who also identified a cluster located in the similar region (with comparable characteristics) and demonstrated the influence of EN and LN on these TCs. Our findings (of Cluster 2 events) also corresponds with notable EN phases and seasons with highest TC counts such as 1981, 1983, 1998, and 2015-2016, reflected in Figures 4a,c, respectively (Yu and Kim, 2013. The TC track regime of Cluster 2 (i.e., increasing trend in the eastern SWP with longer tracks) compares with Sharma et al (2020), given they reported on the east-to-northeasterly modulation of TC genesis and expansion of the decay region in a southeasterly direction.…”
Section: Part A: Characteristics Of Tc Cluster Trajectoriessupporting
confidence: 77%
See 3 more Smart Citations
“…This cluster is consistent with Ramsay et al (2012) who also identified a cluster located in the similar region (with comparable characteristics) and demonstrated the influence of EN and LN on these TCs. Our findings (of Cluster 2 events) also corresponds with notable EN phases and seasons with highest TC counts such as 1981, 1983, 1998, and 2015-2016, reflected in Figures 4a,c, respectively (Yu and Kim, 2013. The TC track regime of Cluster 2 (i.e., increasing trend in the eastern SWP with longer tracks) compares with Sharma et al (2020), given they reported on the east-to-northeasterly modulation of TC genesis and expansion of the decay region in a southeasterly direction.…”
Section: Part A: Characteristics Of Tc Cluster Trajectoriessupporting
confidence: 77%
“…Also, EN phases observed in Figure 4a align with the peaks observed along the Cluster 2 timeline, e.g. , 1981, , 1983, , 1998, and 2015, -2016. Figure 4e shows peaks in Cluster 4 TCs during 1964TCs during , 1985TCs during -1986 and 2016 and a statistically significant decreasing trend.…”
Section: Temporal Trends In Tc Clusterssupporting
confidence: 62%
See 2 more Smart Citations
“…Accurately predicting the migratory track, intensity and rainfall of TCs is a key research focus for meteorologists and weather forecasters [9]. Factors influencing track orientation, shape, sinuosity, and ultimately points of landfall are of particular interest [10,11]. Satellite-based cloud images are useful for analyzing TC cloud structure and dynamics [12][13][14][15][16].…”
Section: Tropical Cyclone Hazardsmentioning
confidence: 99%